Revelation and Knowledge : Romanticism and Religious Faith - Woodman, Ross Greig (Book collections on Project MUSE., 2011)
Ross Woodman's Sanity, Madness, Transformation was an adventurous exploration of the links between madness in Romantic writing and modern literary and psychoanalytic theory. Revelation and Knowledge picks up where his previous work left off by tracing the profound connections and gaps between religious and poetic faith in the works of the British Romantic poets.Woodman and Joel Faflak focus on the clash in these authors' works between depth psychology and mysticism in the context of post-Enlightenment crises of belief. They also delve into the treatment of revelation in Romantic poetry, expanding on the concept through nuanced examinations of specific Eastern and Western religious traditions. Revelation and Knowledge showcases Woodman's trademark ability to combine literary criticism with autobiography, resulting in a surprising work that is also uniquely daring.